Nursing students' perspectives on learning math for medication calculations in a Canadian nursing program in Qatar. (November 2020) - Johnson, J.; Kareem, A.; White, D.; Ngwakongnwi, E.M.; Mohammadpour, M.; Rizkika, N.; Ouattas, R.; Shahrour, Y.; Ali, R.; Roshanuddin, J.
Abstract: This study describes nursing students' perspectives on learning math for medication calculations in a Canadian baccalaureate nursing program in Qatar. There is a dearth of guidance within the nursing literature to support teachers to develop pedagogical methods to help improve students' math competence. Moreover, the challenge of teaching math skills to student nurses in Qatar is particularly difficult because there is little standardization of curricula in secondary education. Data collected from focus groups was analyzed using interpretive description. Focus groups included, Group 1 those students who were beginning to learn math for medication calculations and had not completed the required math module and Group 2, students who had not yet completed the math module. Themes emerging from the data included from first year students, 1. Fear of math resulting in resistance to learning math for medication administration. 2. Student success is dependent on good instructors. 3. Student resentment towards perceived 'complicated' math in the nursing program. Themes from second year students included 1. Lack of nursing student's confidence with medication calculation within the clinical settings 2. Lack of self-directedness to uptake math knowledge 3. Incongruence amongst clinical instructors with applied math practice whilst in the clinical setting. Highlights: This article was part of a UREP project about students and including students. This article highlights issues associated with learning math for medication in hospitals. This article elucidates some key reccomendations for improvment.